DCLK1, a Putative Stem Cell Marker in Human Cholangiocarcinoma. Issue 1 (6th February 2021) - Nevi, Lorenzo; Di Matteo, Sabina; Carpino, Guido; Zizzari, Ilaria Grazia; Safarikia, Samira; Ambrosino, Valeria; Costantini, Daniele; Overi, Diletta; Giancotti, Antonella; Monti, Marco; Bosco, Daniela; De Peppo, Valerio; et al.
Abstract : Background and Aims: Cholangiocarcinoma (CCA) is a very aggressive cancer showing the presence of high cancer stem cells (CSCs). Doublecortin‐like kinase1 (DCLK1) has been demonstrated as a CSC marker in different gastroenterological solid tumors. Our aim was to evaluate in vitro the expression and the biological function of DCLK1 in intrahepatic CCA (iCCA) and perihilar CCA (pCCA). Approach and Results: Specimens surgically resected of human CCA were enzymatically digested, submitted to immunosorting for specific CSC markers (LGR5 [leucine‐rich repeat‐containing G protein‐coupled receptor], CD [clusters of differentiation] 90, EpCAM [epithelial cell adhesion molecule], CD133, and CD13), and primary cell cultures were prepared. DCLK1 expression was analyzed in CCA cell cultures by real‐time quantitative PCR, western blot, and immunofluorescence. Functional studies have been performed by evaluating the effects of selective DCLK1 inhibitor (LRRK2‐IN‐1) on cell proliferation (MTS [3‐(4, 5‐dimethylthiazol‐2‐yl)‐5‐(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenyl)‐2 H ‐tetrazolium] assay, cell population doubling time), apoptosis, and colony formation capacity. DCLK1 was investigated in situ by immunohistochemistry and real‐time quantitative PCR. DCLK1 serum concentration was analyzed by enzyme‐linked immunosorbent assay. We describe DCLK1 in CCA with an increased gene and protein DCLK1 expression in pCCA LGR5+ and in iCCA CD133+ cells compared with unsorted cells. LRRK2‐IN‐1 showed an anti‐proliferative effect in a dose‐dependent manner. LRRK2‐IN‐1 markedly impaired cell proliferation, induced apoptosis, and decreased colony formation capacity and colony size in both iCCA and pCCA compared with the untreated cells. In situ analysis confirmed that DCLK1 is present only in tumors, and not in healthy tissue. Interestingly, DCLK1 was detected in the human serum samples of patients with iCCA (high), pCCA (high), HCC (low), and cirrhosis (low), but it was almost undetectable in healthy controls. Conclusions: DCLK1 characterizes a specific CSC subpopulation of iCCA CD133+ and pCCA LGR5+, and its inhibition exerts anti‐neoplastic effects in primary CCA cell cultures. Human DCLK1 serum might represent a serum biomarker for the early CCA diagnosis.